Radiological Findings of Pulmonary Tuberculosis in Children at Dr. Hasan Sadikin General Hospital Bandung 2018–2019 - Nanda Mia Ghaesani; Ristaniah Rose Effendy; Diah Asri Wulandari (Althea Medical Journal, 2021)
Background: Tuberculosis (TB) remains a major cause of death worldwide, especially in children. Indonesia is ranked second as the largest contributor to TB. Chest X-rays have been used to diagnose pulmonary TB in children, however, the results are varied. Therefore, this study was performed to explore the radiological findings among children with pulmonary TB. Methods: Retrospective descriptive study was conducted by analyzing the chest X-ray findings retrieved from the medical records of all pulmonary TB children treated at Dr. Hasan Sadikin General Hospital during 2018 to 2019. Inclusion criteria were medical records of patients aged 1 month to 18 years diagnosed with pulmonary TB who underwent chest X-ray (n=223).Results: The highest incidence of pulmonary TB was found in the group of 10–18 years (43.9%) and female (50.2%). The results of chest X-ray were infiltrates (65.0%), lymphadenopathy (11.7%), cavity (7.6%), calcifications (7.6%), miliary (4.9%), pleural effusion (3.1%) and atelectasis (1.8%). Conclusion: Infiltrates are the major finding on Chest X-ray in children with TB.